Pharmacokinetics, Pharmacodynamics, and Exposure‐Response of Lanadelumab for Hereditary Angioedema. Issue 6 (26th May 2020) - Wang, Yi; Marier, Jean-Francois; Kassir, Nastya; Chang, Colin; Martin, Patrick
Abstract : Hereditary angioedema (HAE) with C1 inhibitor deficiency is a rare disorder characterized by unpredictable, potentially life‐threatening recurrent angioedema attacks. Lanadelumab is a fully human monoclonal antibody with selective binding to active plasma kallikrein, and prevents the formation of cleaved high molecular weight kininogen (cHMWK) and bradykinin, thereby preventing HAE attacks. The clinical pharmacology of lanadelumab was characterized following subcutaneous administration in 257 subjects (24 healthy subjects and 233 patients with HAE). The pharmacokinetics of lanadelumab were described using a one‐compartment model with first‐order rate of absorption and linear clearance, showing slow absorption and a long half‐life (14.8 days). A covariate analysis retained body weight and health status on apparent clearance (CL/F) and body weight on volume of distribution (V/F). Population estimates of CL/F and V/F were 0.0249 L/hour (0.586 L/day) and 12.8 L, respectively. An indirect‐response Imax model showed 53.7% maximum suppression in cHMWK formation with a low potential for interactions with concomitant medications (analgesic, anti‐inflammatory, and antirheumatic medications). A 300 mg dose administered Q2W was associated with a mean steady‐state minimum concentration (Cmin, ss ; 25.4 μg/mL) that was 4.5‐fold higher than the half‐maximal inhibitory concentration for cHMWK reduction (5.71 μg/mL). Exposure‐response analyses suggest that 300 mg Q2W dosing was associated with a significantly reduced HAE attack rate, prolonged time to first attack after treatment initiation, and lower need for concomitant medications. The response was comparable across patient body weight groups. Findings from this analysis support the dosing rationale for lanadelumab to prevent attacks in patients with HAE.